Mengajar Anak Secara Profesional: Suatu Tuntutan bagi Guru Sekolah Minggu di Abad 21 - Gea, Leniwan Darmawati (SAINT PAUL'S REVIEW, 2024)
Sunday School service is one of the categorical services in the church which is very important, but is often not handled by teachers or instructors who are well competent compared to services for adults. In fact, they are the next generation who are expected to continue the existence of the church. This is very worrying based on the author's observations in several churches served by STT ATI students. The subjects of this research were STT ATI students. The aim of this research is to investigate the reality of Sunday school services with their various difficulties, as well as to encourage the need for professionally trained teachers in the midst of 21st century developments to play an effective role in serving Sunday School children. The research method used is qualitative research with a phenomenological approach to explore and describe sources of information from informants according to the main problem being studied. The results of this research are that professional Sunday School teacher figures are very much needed in the midst of increasingly advanced developments, especially in the digital era of the 21st century. To achieve this, training for Sunday School teachers is very effective in forming school teachers. A creative and innovative week.